Sistem Penjualan Pasar Cihapit Kota Bandung Ditinjau Dari Aspek Digitalisasi Pasar Rakyat - Siti Nurhaliza; Eka Yulyana; Sopyan Resmana Adiarsa (Peneliti.net, 2023)
People's Market is a place of business that is managed, built, and managed by the government, local government, private sector, State-Owned Enterprises (BUMN), and/or Regional-Owned Bada Usama (BUMD), can be in the form of shops/kiosks, stalls and tents. owned/managed by small and medium-sized traders, non-governmental organizations, or cooperatives as well as MSMEs with the process of buying and selling goods through bargaining. Traders of the Cihapit Market in Bandung City have felt the impact of the COVID-19 pandemic, such as the decline in the number of consumers and the regulation of people's market operating hours. The research approach used is a qualitative approach